Aside from the norm: artistic sexual/gender dissent and nonnormative formations in Ukraine. - Dmytryk, Olena (Apollo - University of Cambridge Repository, 2022)
This thesis is an interdisciplinary contribution to the historical and cultural sociology of (nonnormative) sexuality and gender in Ukraine. It engages with figures and collectives situated what I describe as ‘aside from the norm’ in terms of their transgression of the gender/sex system, and in the sense of their complex relationship with the institutionalized art system. Turning to ‘artistic sexual/gender dissent’ in this regard opens a discussion on what is considered ‘dissenting’ in terms of sexuality and gender, and how such artistic dissent is related to the various nonnormative formations in Ukraine. The first line of inquiry is related to Ukraine’s development as a nation-state, and the influence that political and economic shifts had on the construction of new social formations and subjects considered normative or nonnormative. By analysing artistic works and the nonnormative social formations to which they point, I trace the development of various forms of political activism in Ukraine since 1990s, keeping in touch with concealed or forgotten pasts and radical possibilities. In parallel with the exploration of nonnormative formations in Ukraine (such as specific communities, circles, networks of dissent, existing or imagined), I investigate social formations involved in the production and managing of ‘nonnormativity’ in Ukraine. The second line of inquiry is related to the analysis of artistic works as such. The themes, artistic strategies and aesthetic devices deployed to document or imagine nonnormative experiences and dissenting standpoints are investigated. Exploration of opposition to sexual/bodily shame, figurations of nonnormativity, dis-identification with modernity and ‘traditions’ in artistic works allows a greater understanding of the aesthetic, political, and social specificity of artistic sexual and gender dissent in Ukraine.
Keywords: slavonic studies; slavic studies; ukrainian studies; art; identity; Russo-Ukrainian war; Ukraine; contemporary art; postcolonialism; postsocialism; decolonial; temporality; poetry; performance; musicology; street art; LGBT; queer; transgender; activism; artivism; feminism; social movements; morality; anti-gender movements; gender ideology; far right; Europeanisation; neotraditionalism; modernity; textile art